Methods of reconstruction of large-scale residential development areas - Chui , Yana; Kamalova, Klavdia; Kukina, Irina (project baikal, 2023)
The areas of large-scale residential development are becoming less and less suitable for modern requirements for high quality and comfort of the residential and urban environment. The main disadvantages of the residential areas are physical and moral deterioration of the building, degradation of adjacent territories, as well as outdated functional and planning morphology. The authors study the methods to create an individual algorithm for reconstruction of such areas. The example of micro-districts of Krasnoyarsk illustrates the methods of reconstruction with the preservation of the form and renewal of the content of territories with a predominance of large-scale residential development
Keywords: large-scale residential development; prefabricated heritage; micro-district; residential environment; program of the renovation; reconstruction of residential areas; Krasnoyarsk